The construction of single-layer two-dimensional supramolecular organic frameworks in water through the self-assembly of rigid vertexes and flexible edges1. Issue 11 (21st March 2015) - Zhang, Xiang; Nie, Cheng-Bin; Zhou, Tian-You; Qi, Qiao-Yan; Fu, Jie; Wang, Xiao-Zhong; Dai, Liyan; Chen, Yingqi; Zhao, Xin
<x xml:space="preserve">Abstract</x> Single-layer two-dimensional supramolecular organic frameworks were constructed through self-assembly of rigid vertexes, flexible edges, and cucurbit[8]uril hosts.